Evidence of inflated exclusive breastfeeding estimates from a clinical trial in Bangladesh - Thomas J. Roberts; Yana E. Hoy-Schulz; Kaniz Jannat; Julie Parsonnet (BMC, 2018)
Abstract Suboptimal breastfeeding is a major cause of infant morbidity and mortality across the world. Inconsistent data has hampered quantification of this practice, however, limiting breastfeeding promotion efforts. As part of a clinical trial in Dhaka, Bangladesh, data was collected on breastfeeding patterns among 125 infants. Infants were ages 4 to 12 weeks (mean = 8.05, SD = 2.13) at the time of enrollment, and breastfeeding data were collected at 24 study visits during a twelve-week period. Breastfeeding status was assessed using the WHO-recommended "current status" (24-h recall) method. These data were used to calculate two measures: a longitudinal estimate of exclusive breastfeeding since birth and a simulated cross-sectional prevalence to approximate common data collection methods. Infants were then ranked based on their breastfeeding status at all study visits and grouped into quartiles and compared using hospitalization data recorded for all infants as part of the original study. These data showed large differences in estimates of exclusive breastfeeding behaviors when assessed longitudinally (8.8% exclusive breastfeeding) vs. calculating a cross-sectional prevalence (56.2% exclusive breastfeeding). Additionally, when infants were grouped by quartile of breastfeeding behavior and matched with hospitalization records, it was found that infants in the lowest quartile of breastfeeding behaviors were significantly more likely to be hospitalized than infants in the highest quartile. These results provide further evidence that current breastfeeding epidemiology studies may overestimate rates of exclusive breastfeeding. They also provide further evidence to support the significant infant health benefits from breastfeeding promotion. Trial registration: ClinicalTrials.gov NCT01899378. Registered July 10, 2013.